Pengaruh Kompensasi Finansial dan Non Finansial terhadap Loyalitas Karyawan pada PT Bali Hastie Indomalaya - Muh. Arham Hidayat; Andi Mustika Amin; Rezky Amalia Hamka; Muhammad Ichwan Musa; Uhud Darmawan Natsir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Employe loyalty is a crucial aspect in maintaining the stability and operational effectiveness of a company, especially amidst the ever-evolving dynamics of business competition. Companies are required to manage human resources optimally by providing compensation that is not only financial but also non-financial, as a form of recognition for employe contributions. Both forms of compensation are believed to play an important role in building a sense of belonging, commitment, and employes' willingness to stay with the company. Based on this urgency, this study aims to analyze the influence of financial and non-financial compensation on employe loyalty at PT Bali Hastie Indomalaya, both partially and simultaneously. The research used a quantitative approach with a cross-sectional method, involving 104 employes as respondents who completed closed and open questionnaires. Data analysis was conducted using multiple linear regression thru SPSS software. The research results indicate that financial compensation has a positive and significant effect on employe loyalty. Additionally, non-financial compensation has also been proven to have a positive and significant impact, particularly thru aspects of the work environment, communication, and relationships between employes. Simultaneously, both forms of compensation have a positive and significant impact on employe loyalty. This finding indicates that the combination of material and non-material compensation is very important in building loyalty and work commitment at PT Bali Hastie Indomalaya.